Physical and computational analysis of the yeast Kluyveromyces lactis secreted proteome - Swaim, C.L.; Anton, B.P.; Sharma, S.S.; Taron, C.H.; Benner, J.S.
Secretion of proteins is the most common approach to protein expression in Kluyveromyces lactis. A proteomic analysis was performed on spent fermentation medium following bioreactor propagation of a wild-type industrial strain to identify proteins naturally secreted by K. lactis cells. Multidimensional separations were conducted and RP online ESI-MS/MS analysis identified 81 secreted proteins. In addition, an in silico analysis predicted 178 K. lactis proteins to be secreted via the general secretory pathway (GSP). These two datasets were compared and approximately 70
Keywords: ESI-MS/MS; KLUYVEROMYCES LACTIS; MULTI-DIMENSIONAL; SECRETOME